Does art therapy need a theory? - Wita Szulc (Studia Paedagogica Ignatiana, 2021)
The author discusses Polish publications on the theoretical foundations of art therapy published in Poland in chronological order and confronts them with the world literature of Art Therapy. One of the problems discussed in this paper is plagiarism in the Polish literature on Art Therapy, which is an obstacle on the way to Art Therapy achieving the status of science. The article covers such issues as sources of knowledge about Art Therapies, terminology, types, models and paradigms of Arts therapy. The aim of this article is to draw attention to the need for a critical approach to the available and disseminated sources of knowledge about the theory.